Implementing Citrix XenDesktop on IBM Flex System - Krutov, Ilya (IBM redbooks., 2014)
The IBM SmartCloud Desktop Infrastructure offers robust, cost-effective, and manageable virtual desktop solutions for a wide range of clients, user types, and industry segments. These solutions help to increase business flexibility and staff productivity, reduce IT complexity, and simplify security and compliance. Based on a reference architecture approach, this infrastructure supports various hardware, software, and hypervisor platforms. The SmartCloud Desktop Infrastructure solution with Citrix XenDesktop running on IBM Flex System offers tailored solutions for every business, from the affordable all-in-one Citrix VDI-in-a-Box for simple IT organizations to the enterprise-wide Citrix XenDesktop. XenDesktop is a comprehensive desktop virtualization solution with multiple delivery models that is optimized for flexibility and cost-efficiency. This IBM Redbooks publication provides an overview of the SmartCloud Desktop Infrastructure solution, which is based on Citrix XenDesktop running on IBM Flex System. It also provides planning and deployment considerations, and step-by-step instructions about how to perform specific tasks. This book is intended for IT professionals who are involved in the planning, design, deployment, and management of the IBM SmartCloudʼ Desktop Infrastructure built on IBM Flex System running Citrix XenDesktop. --